Unveiling COVID-19’s impact on Financial Stability: A Comprehensive Study of Price Dynamics and Investor Behavior in G7 Markets - Talbi, Mariem; Ferchichi, Monia Mokhtar; Ismaalia, Fatma; Samil, Samia (International Journal of Economics and Financial Issues, 2024)
The paper delves into the impact of the COVID-19 pandemic on foreign stock markets across several developed nations. It seeks to empirically validate the presence of contagion by employing an adjusted correlation test spanning 7 developing stock markets from February 1, 1992, to April 31, 2021. Employing the FIEGARCH (1.1), DCC-MGARCH(1,1), and Switching-Markov analysis models, the research uncovers compelling evidence of the pandemic’s influence on most developed countries during the COVID-19 period. Notably, these markets appear significantly susceptible to the adverse effects brought about by the pandemic. Recognizing the substantial ramifications of financial downturns on monetary policy, risk assessment, asset valuation, and portfolio distribution, the findings hold paramount significance for policymakers, investors, and portfolio managers. This empirical investigation offers insights that could profoundly impact decision-making strategies in these domains, shedding light on crucial aspects for informed policy adjustments, investment decisions, and portfolio allocations amidst such critical market fluctuations.